Self-employment as a stepping stone to better labour market matching: a comparison between immigrants and natives - Magdalena Ulceluse (Global Labor Organization (GLO), 2018)
The paper investigates whether self-employment represents a way to reduce overeducation and improve labour market matching, in a comparative analysis between immigrants and natives. Using the EU Labour Force Survey for the year 2012, and controlling for a list of demographic characteristics and general characteristics of 30 destination countries, I find that the likelihood of being overeducated decreases for self-employed immigrants, with inconclusive results for self-employed natives. The results shed light on the extent to which immigrants adjust to labour market imperfections and barriers to employment and might help explain the higher incidence of self-employment that immigrants exhibit, when compared to natives. This is the first study to systematically study the nexus between overeducation and self-employment in a comparative framework. Moreover, the paper tests the robustness of the results by employing two different measures of overeducation, contributing to the literature of the measurement of overeducation.
Keywords: J15; J24; J61; 330; self-employment; immigrants; skills mismatch; overeducation